2019
DOI: 10.1111/ajco.13275
|View full text |Cite
|
Sign up to set email alerts
|

Hematological toxicities associated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy

Abstract: Introduction Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have been found to prolong survival in selected patients with peritoneal disease, but the extent of cytoreduction and chemoperfusion can result in systemic toxicities. We evaluate the incidence of perioperative hematological complications and its associated risk factors. Methods Retrospective analysis of a prospectively collected database of CRS‐HIPEC cases between April 2001 and October 2016 was performed. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…Contrary to previously published reports, we present a case of pancytopenia in a patient who underwent splenectomy as part of CRS and subsequent MMC-HIPEC. One retrospective analysis by Wong et al, [13] showed that while neutropenia and thrombocytopenia can occur postoperatively, the median duration was only 1 and 3 days, respectively, which is significantly shorter than that seen in our patient.…”
Section: Discussioncontrasting
confidence: 78%
“…Contrary to previously published reports, we present a case of pancytopenia in a patient who underwent splenectomy as part of CRS and subsequent MMC-HIPEC. One retrospective analysis by Wong et al, [13] showed that while neutropenia and thrombocytopenia can occur postoperatively, the median duration was only 1 and 3 days, respectively, which is significantly shorter than that seen in our patient.…”
Section: Discussioncontrasting
confidence: 78%
“…We also found a trend towards a longer ICU stay in patients who developed leukopenia, as already described by other authors [24,31].…”
Section: Discussionsupporting
confidence: 90%
“…Only two studies— one involving 18 patients treated with intravenous ifosfamide and HIPEC and the other involving 50 patients treated with CRS and HIPEC—described an incidence of 61.1 and 36%, respectively, with a cut-off of 150,000/mm 3 as in our study [ 22 , 23 ]. Another described an incidence of thrombocytopenia (defined as lower than 140,000/mm 3 ) of 37.9% in 235 CRS and HIPEC patients; these authors found that increased age (>60 years) and previous chemotherapy were independent risk factors associated with the development of thrombocytopenia [ 24 ]. Although we did not reach such a finding, severe thrombopenia (less than 50,000/mm 3 ) is described in 0.6–11% of patients [ 7 , 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation